Remained Insect's Body Part in the Corneal Stroma: A Rare Case Report - Abdillah, Fauzi; Widyanto, Ilham Aditya; Ariany, Dessira Rizka Tri (Jurnal Kedokteran Brawijaya, 2025)
Corneal foreign bodies are the second most common cornea disease after corneal abrasion. The causes of foreign bodies in the cornea vary, most often due to lack of eye protection. Patients with foreign bodies in the cornea usually complain pain, a lump in the eyes, visual acuity deficit, watery eyes, red eyes, sticky eyes, and photophobia. Rapid and effective treatment is needed to avoid the risk of worsening the patient's condition and decreasing vision or even permanent blindness. In this case, we report a 41-year-old male who suffered an eye injury due to insect's body parts remaining in the corneal stroma while riding a motorbike. Foreign body extraction, eye irrigation, topical and systemic antibiotics and steroids, topical cycloplegic are the various treatment modalities for better result. Further examination could be done to find out the chemical elements of insect's toxin so that more adequate therapies can be given.